دور األحزاب السياسية في تنمية الحس السياسي وترسيخ قيم المواطنة في الجزائر - بن ناصرنجاة  حاجيح دلال (جامعة المسيلة, 2024)
تعد األحزاب السياسية من أدوات التنمية السياسية في العصر الحديث، وعلى اعتبار أن فعالية سياسة التصنيع تعبر عن مضمون التنمية السياسية واالقتصادية، فإن حركية األحزاب السياسية والنظام الحزبي تعبر بالمقابل عن درجة التنمية السياسية داخل النظام السياسي وداخل الدولة. لقد حافظت األحزاب السياسية في الجزائر على أهميتها بالرغم من تطور مؤسسات المجتمع المدني التي ً على الصعيد الخارجي من خالل التحالفات اكتسببعضها مرك از ، ولكن تلك المؤسسات لم تستطع ً مرموقا أن تؤدي وظيفة األحزاب في عملية التداول السلمي على السلطة، باإلضافة إلى وظائفها األخرى داخل المجتمع، ولقد توضح لدينا من خالل هذه الدراسة أن أدوار األحزاب السياسية في التنمية السياسية عن طريق ترسيخ قيم المواطنة وتنمية الحس السياسي تتأثر بصفة مباشرة بأدوارها داخل التحالفات السياسية الحزبية، فمعظم االحزاب السياسية الجزائرية وجدنا أنهاتسير في طريق مغلق نتيجة التنافس والصراع الحاد بين زمرة السياسية وكحتمية لطبيعة النظام السياسي المنغلق الذي ال يسمح بالحراك السياسي داخل النخب ً على مردود أح ازب السياسية مجتمعة على المستوى المحلي والوطني. السياسية. وهو األمر الذي أثرسلبا الكلمات المفتاحية:األحزاب السياسية، المواطنة، الحس السياسي. Abstract: Political parties are among the tools of political development in the modern era، and given that the effectiveness of the industrialization policy expresses the content of political and economic development، the dynamism of political parties and the party system، in return، expresses the degree of political development within the political system. Political parties in Algeria have maintained their importance despite the development of civil society institutions، some of which have gained a prominent position on the external level through alliances. However، these institutions were unable to perform the function of parties in the process of peaceful transfer of power، in addition to their other functions within society. Through this study، it has become clear to us that the roles of political parties in political development by consolidating the values of citizenship and developing political sense are directly affected by their roles within partisan political alliances. We found that most of the Algerian political parties are on a closed path as a result of the intense competition and conflict between the political faction and as an inevitable nature of The closed political system that does not allow political movement within the political elite. This negatively affected the performance of all political parties at the local and national levels. keywords: Political parties، citizenship، political sense.
Keywords: الكلمات المفتاحية:األحزاب السياسية، المواطنة، الحس السياسي.